Respostas

2014-07-16T23:10:08-03:00
A) 4x²-36=0          b)x²+x              c)Δ=b²-4ac
    4x²=36               x(x+1)=0          Δ=(-4)²-4.1.4                                       a=1
     x²=36/4             x=0                 Δ=16-16                                            b=-4
     x²=9                  x+1=0             Δ=0                                    x'=4/2=2      c=4         x=√9                   x=-1            x=-b+-√Δ x= -(-4)+-√0= 4+-0=
     x=3                                              2.a            2.1           2       x'''=4/2=2